High NT pro-BNP levels in children with malignant disorder receiving intensive fluid treatment: a prospective comparative study - Pawlik, Weronika; Strzemecka, Joanna; Stachura, Albert; Królak, Aleksandra; Ociepa, Tomasz (Frontiers in Pediatrics, 2024)
Hematologic malignancies are a well-known risk factor for cardiovascular disease development. Chemotherapeutic protocols commonly include intensive fluid therapy (IFT), which may negatively influence the cardiovascular system and predispose to arterial hypertension. This study aims to evaluate atrial natriuretic peptide (NT-proBNP), high-sensitivity troponin T (hs-TnT), and changes in blood pressure in children with hematological malignancies undergoing intensive fluid therapy. This prospective cohort study comprised thirteen children. 24-hour ambulatory blood pressure monitoring (ABPM) and concentrations of NT-proBNP and hs-TnT were performed on the first day of IFT and during follow-up. There were no statistically significant differences in 24-hour, daytime, night-time systolic (SBP) and diastolic blood pressure (DBP), SBP and DBP dipping, and the number of nondippers during intensive fluid therapy compared to the control points. The mean NT-proBNP concentration at 24 hour was 321.27 ± 318.08 pg/ml and was significantly higher compared with baseline (79.13 ± 105.42 pg/ml) and follow-up (175.92 ± 241.48 pg/ml); p values 0.005 and p=0.006 respectively. Troponin T concentration at 24 hour was not significantly different compared with baseline and follow-up. These results show no significant influence of intensive fluid therapy on blood pressure profile. In contrast, an increase in NT-proBNP values 24 hours after the start of fluid therapy may reflect the impact of fluid overload on the cardiovascular system.